Accelerated Access to Medicines: An Ethical Analysis. (March 2017) - Pace, Jessica; Ghinea, Narcyz; Kerridge, Ian; Lipworth, Wendy
In recent years, a range of initiatives have been introduced to provide patients with access to medicines outside of traditional regulatory and/or funding channels; we term these processes "accelerated access to medicines." These generally take 1 of 3 forms: those that provide access by making existing regulatory and funding processes more efficient, those that provide access despite uncertainties surrounding safety or efficacy, and those that provide access despite uncertainties surrounding cost-effectiveness. These latter 2 types are the subject of intense debate, as they generally require us to suspend or override accepted standards of evidence of safety, effectiveness, and/or cost-effectiveness. Ethical analysis provides valuable insights into these debates and highlights the risks and benefits that may accrue as a consequence of different accelerated access schemes. In this article, we use the principle-based approach to ethical analysis described by Beauchamp and Childress (sometimes called the "four principles approach" because it frames analysis by reference to beneficence, non-maleficence, autonomy, and justice) to analyze initiatives that provide accelerated access to medicines. We identify a number of ethical issues that may arise in the context of accelerated access initiatives, including potential patient harms, impacts on patient autonomy and informed consent, and effects on research and regulatory systems. The complex ethical issues at play emphasize that there is no single answer to questions as to whether such schemes are "ethical"; rather, ethical principles will need balancing, context will be critically important, and discussion among the various stakeholder groups will be needed to reach an "ethically good" outcome.